Influence of the pavement solar collector system on the urban environment - Xu, Weijie (2024)
The Urban Heat Island (UHI) phenomenon has been a concern for many cities worldwide, and it is getting more severe with the development of urbanisation. Asphalt can absorb a large amount of heat due to its high heat capacity, and excessive heat will be released into the air, aggravating the UHI effect. The cool pavements showed a higher potential than other heat mitigation methods in resolving the urban overheating issue. Pavement Solar Collector (PSC) is a system that allows excessive heat to be transferred from the pavement surface to the bottom layers and then absorbed by the circulating fluid in the copper pipes; the absorbed heat can be converted into passive thermal energy, stored in the thermal reservoir and utilised for other purposes.